Haematological changes in experimental haemonchosis in Barbari goats - SHARMA, D K; CHAURAN, P P S; AGRAWAL, R D (The Indian Journal of Animal Sciences, 2013)
The information on caprine haemonchosis is meagre. Therefore, present study was made to study the haematologlcal changes in experimental Haemonchus contortus infection m Barbari goats. The 12 male goats of 6-9 months age were divided in 2 groups A and B having 8 infected and 4 control ammals respectively. Selected animals were first screened and made free from any endoand eeto-parasites. These were kept under strict hygienic conditions and provided with clean water and tree tops without any grazing. The animals in group A, were administered with 5 000 L3 (H. contortus) orally, while those in group B were kept as uninfeeted control. Both the groups were bled every week and blood samples were examined for haematologlcal parameters, viz. pev, Rb and TEe and erythrocytic indexes of MeV, MCR and MeRe were worked out. Statistical analysis oftbe data revealed significant fall of PCV, Hb, and TEe in infected goats when compared with control indicating anaemia marked by no appreciable change in MCV artd thus absence of reticulocytosis. Pathogenesis of anaemia was attributed to haemorrhage and haemodilution after infection.